Study of the reaction for PIGE applications - K. Preketes-Sigalas; A. Lagoyannis; M. Axiotis; S. Harissopulos; Kokkoris, M.; Mertzimekis, T. J.; V. Paneta; G. Provatas (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2016)
Abstract The differential cross sections of the 2125 keV $γ$–ray, emitted by the $^{11}$B(p, p'$γ$)$^{11}$B reaction were measured at six (6) angles and at proton energies from 2.5 to 5.0 MeV. The experimental setup consisted of three (3) 100% relative efficiency \{HPGe\} detectors placed on a motorized turntable. The comparison between the present measurements, which have an overall uncertainty of $\sim$8%, and previous ones from literature gives contradictory results. While there are large differences with previous differential cross-section measurements from literature, there is good agreement with previous thick-target yield ones. Additional thick-target measurements were performed in an effort to explain the observed discrepancies.
Keywords: 11B; Differential cross section; PIGE